ANTECEDENTS OF WOMEN'S INNOVATION CAPABILITY IN MEDAN: THE MEDIATION ROLE OF KNOWLEDGE MANAGEMENT CAPABILITY - Anggia Sari Lubis; Debbi Chyntia Ovami; Arif Qaedi Hutagalung; Fairuz Shofie Nasution; Azzahra Adelia (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2024)
The role of Small Micro Entreprises (SMEs) in supporting the country's economy means that SMEs are increasingly being paid attention and really important by the government. As many as 64.5 percent of the total small, micro and medium enterprises MSMEs) in Indonesia are women. The innovation capability of micro, small and medium enterprises MSMEs) is a major factor in business sustainability. However, in reality, women entrepreneur only focus on product and service creation activities without providing any innovation. Most MSMEs produce products that suit their production capabilities without paying attention to the needs and wants of consumers who of course expect innovation and something in the products produced. The purpose of this paper is to analyze the influence of factors that affect knowledge management capability (KMC) as well as analyzing the mediating factors that influence the relationship of factors such as information technology relatedness, knowledge sharing and human resource management capability on innovation capabiity. This research is a quantitative research with descriptive statistics. The analytical tool used is a structural equation model of partial least squares (PLS). This research was conducted on women entrepreneur in Medan Using a proportional random sampling technique, 200 respondents of employees were selected. The results of this study are as follows: (1) information technology relatedness, knowledge sharing and human resource management capability have a significant effect on knowledge management capabilty; (2) knowledge management capability, information technology relatedness and human resource management capability have a significant effect on innovation capability; (3) knowledge management capability have a significant effect on innovation capability; (4) information technology relatedness has a significant effect on innovation capability through knowledge management capability; (5) knowledge sharing has a significant effect on innovation capability through knowledge management capability; (6) human resource management capability has a significant effect on innovation capability through knowledge management capability.